High School Teachers' Perceptions of the Influence of Social Media on Students' Development and Learning Activities at School - Scolastika, Fitriana; Mariyadi; Amir, Amriani (Universitas Pendidikan Ganesha, 2025)
The development of technology has a significant impact on the way humans interact, such as the use of social media. In fact, many teenagers have not been able to control their use properly, thus affecting their academic environment. This study aims to analyse teachers' perceptions of the influence of social media on students' development and learning activities at school. This study used a qualitative method with a phenomenological design, involving eight teachers who were selected according to the research criteria. Data were collected through semi-structured interviews using interview guidelines supported by a voice recorder. Data analysis used thematic analysis techniques. This study successfully revealed four themes, namely the usefulness, sub-themes of More Interactive Learning, Easy to Disseminate Information, Easy to Manage Assignments and Easy to Conduct Assessments, and Improved Student Competence, Negative Impacts sub-themes of Addiction, Cyberbullying, Plagiarism, Unfocused Learning, and Indifferent Attitudes to Assignments, Barriers sub-themes of Facility Barriers and Competency Barriers, and Recommendations sub-themes of Used to Share Information, Used for Teaching Media, Scheduled Use, and Need for Training. Overall, teachers view social media as having a two-way impact, namely positive and negative depending on self-control of its use. If used appropriately, social media can support the learning process.